Calix[4]crowns with perfluoroalkylsulfonylcarboxamide functions: a complexation approach for heavy group 2 metal ions. Issue 2 (5th December 2022) - Reissig, Falco; Bauer, David; Al-Ameed, Karrar; Luber, Sandra; Köckerling, Martin; Steinbach, Jörg; Pietzsch, Hans-Jürgen; Mamat, Constantin
Abstract : A facile preparation of deprotonizable calix[4]crowns with enhanced properties to stably coordinate Ba 2+ and Ra 2+ inclusive radiolabeling is described. Binding properties of these ions were investigated by DFT calculations to support the findings. Abstract : Heavy alkaline earth metals offer radionuclides which are promising candidates for radiopharmaceutical applications like the γ-emitter barium-131 for diagnosis or the alpha-emitters radium-223/-224 – with similar chemical properties to barium – for targeted alpha-particle therapy. However, there is a lack of suitable chelation agents, especially for these metal ions. A series of calix[4]crown-6 derivatives with perfluoroalkylsulfonylcarboxamide functions (RF = CF3, C2 F5, i -C3 F7, n -C4 F9 ) was synthesized to serve as cage-like chelators for Ba 2+ and Ra 2+ to determine the complexation behaviour. These functional ligands are deprotonated even at slightly acidic pH due to the intense electron-withdrawing effect of the sulfonamide groups. The obtained ligands were easily converted to the desired barium complexes as well as into calix-crown compounds containing two sodium ions. DFT calculations were used to discover the binding behaviour of the metal ions with the desired ligands and the influence of the different donor groups from the chelating moiety of the calixarenes with respect to different pH. Radiolabeling procedures with the radionuclides barium-133 and radium-224 as [ 133 Ba]BaCl2 and [ 224 Ra]Ra(NO3 )2 were performed to determine association constant values between 4.1 and 8.2 for the appropriate M 2+ complexes using a two-phase extraction procedure. A stability test using physiological Ca 2+ solution showed a minor release of approx. 1–7% of the central ions (Ba 2+ respectively Ra 2+ ) from the complexes.